(3ZfjI GdTghGJ aj Led GdGOhGJs - (3CHh fUQ Hf UGYO GdGdeYjs ((3eMeO Hf CHj GdaVd GdUGFZi s)
(3ChdgG (B:s
(3Cbhd HYO MeO Gddg GdPi ecf GdYbd ai Md YbO GdeTcdGJ ef GdhUhd Edi CbUi GdZGjGJ Efi deG QCjJ GdWGFaI eMJGLI Edi cJGH LGeY ai GdGOhGJ s
(3BNQgG (B:s
(3UGOh VGO hWG hXG hOGd hPGd hRGi hKGA fMh EUWHQ h EVWQH hGWdY hCXde hGOQY hGPcQ hGf RLQ hGKYQ Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(1511) s
Keywords: (3GdfMhs